Photosynthetic product allocations of Pinus massoniana seedlings inoculated with ectomycorrhizal fungi along a nitrogen addition gradient - Pengfei, Sun; Yafei, Shen; Lijun, Wang; Tian, Chen; Meng, Zhang; Wenfa, Xiao; Ruimei, Cheng (Frontiers in Plant Science, 2022)
Quantifying the allocation of photosynthetic products among different carbon (C) pools is critical for understanding and predicting plant C turnover response to climate change. A field experiment with ectomycorrhizal fungi (EMF) and nitrogen (N) was established to investigate the effects on allocation of photosynthetic products in Pinus massoniana (Lamb.) seedlings given increased N deposition. Seedlings were subjected to N addition and symbiosis with EMF, and the short-term allocation of a 13C photosynthetic pulse into leaves, branches, stems, roots, and soil was traced. Photosynthetic rate and root respiration were measured. It was found that N addition changed the allocation pattern of photosynthetic products in various organs of P. massoniana. Furthermore, N addition, mycorrhizal symbiosis, and interaction of N and EMF, all increased the amount of C produced by photosynthesis. N application less than 60 kg N hm–1 a–1 could promote the transfer and allocation of photosynthetic products in P. massoniana organs, which peaks at 60 kg N hm–1 a–1, and the highest N treatment began to decrease at 90 kg N hm–1 a–1. EMF inoculation could expand the absorption area of plant roots to obtain more nutrients and synthesize more C and N compounds for promoting the growth of itself and the host plant, improving the net photosynthetic rate and the distribution of C produced by photosynthesis in various organs. This forms a benign C and N cycle, thereby reducing the effect of high N addition on plants. The optimal N addition concentration was 60 kg N hm–1 a–1, and the optimal EMF was Pt, which provides a theoretical basis for inoculating EMF during increasing N deposition in the future climate change scenario. This enables plants to distribute more photosynthetic products to their roots, thus affecting their own C distribution for promoting growth.